Ответы и объяснения

2013-02-18T13:01:15+00:00

1) 2y²(2y-3)+y(2y-3)-(2y-3)=0

(2y-3)(2y²+y-1) = 0

Каждый множитель приравниваем к нулю.

2у-3=0

2у=3

у1=3/2=1,5

 

2y²+y-1 = 0

Д = 1-4*2*(-1)=1+8=9

у2=(-1+3) / 4 = 2/4=1/2=0,5

у3 = (-1-3) / 4 = -1

Ответ: 1,5;  0,5;  -1.

 

2) (6x-1)(x-2)=5(x-2)^2

6x²-12x-x+2=5(x²-4x+4)

6x²-12x-x+2=5x²-20x+20

6x²-12x-x+2-5x²+20x-20=0

x²+7x-18=0

D = 49 - 4*1*(-18) = 49 + 72 = 121

x1 = (-7+11) / 2 = 2

x2 = (-7-11) / 2= -9

ответ: 2 и -9

 

\frac{ xy+1+x+y}{xy+x} = \frac{ x(y+1)+(1+y)}{x(y+1)} = \frac{ (y+1)(x+1)}{x(y+1)} = \frac{x+1}{x}